2015
DOI: 10.1123/ijspp.2014-0498
|View full text |Cite
|
Sign up to set email alerts
|

Different Muscle-Recruitment Strategies Among Elite Breaststrokers

Abstract: The main muscle activities were observed during PP to perform powerful lower-limb extension. The most-skilled swimmer (S1) was the only 1 to solicit her muscles during GP to actively reach better streamlining. Important activation peaks during RP correspond to the limbs acting against water drag. Such differences in EMG strategies among an elite group highlight the importance of considering the muscle parameters used to effectively control the intensity of activation among the phases for a more efficient breas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 0 publications
0
8
0
7
Order By: Relevance
“…All of the swimmers showed coactivation in biceps and rectus femoris during the leg-propulsion phase, indicating that knee extension was generated with high power. High angular velocities for the knee during this phase in breaststroke corresponded to a powerful extension 15 and could be considered a strategy for better controlling the precision and safety of the movement.…”
Section: Biceps Femoris (Long Head) and Rectus Femorismentioning
confidence: 99%
See 1 more Smart Citation
“…All of the swimmers showed coactivation in biceps and rectus femoris during the leg-propulsion phase, indicating that knee extension was generated with high power. High angular velocities for the knee during this phase in breaststroke corresponded to a powerful extension 15 and could be considered a strategy for better controlling the precision and safety of the movement.…”
Section: Biceps Femoris (Long Head) and Rectus Femorismentioning
confidence: 99%
“…That Olympic swimmer also showed higher and earlier activity in the biceps brachii (long head) during the pull phase to perform the elbow-up pull with earlier elbow flexion to achieve large propulsion. A study of lower-limb flexion-extension in the contemporary breaststroke 15 found different muscle activation among international-and national-level swimmers to produce similar movements. The international-level swimmer was the only 1 to maintain muscle activity during the gliding phase to actively reach a better streamlined position to limit drag increase.…”
mentioning
confidence: 99%
“…O modelo esclareceu a capacidade dos nadadores de moderar o aumento do trabalho interno em altas frequências. 42 1 nadadora (internacional); 2 nadadores (nacional)…”
Section: Cálculos De Dinâmicaunclassified
“…A duração total da propulsão de braços e pernas foi avaliada por um novo índice de propulsão de peito plano (IFBP). 5,12,19,20,23,27,36,38,42,53 acabaram por avaliar poucos indivíduos; isso se deve ao fato de que, no ambiente aquático, as pesquisas tornam-se difíceis de serem realizadas. 63 Quanto às produções, no decorrer e a utilização de centrais inerciais 11,18,28,38 que permitem a coleta de variáveis, por telemetria e instantaneamente.…”
Section: Cinemáticaunclassified
“…Como forma de deslocar-se em meio aquático, os nadadores experimentam forças as quais não vivenciam em terra (MAGLISCHO, 2013). Por exemplo, nadadores de diferentes nados realizam tarefas motoras distintas para se deslocar com maestria, aplicando forças em diferentes direções para criar impulso (GUIGNARD et al, 2015;SAMSON et al, 2017 (CORDEIRO et al, 2007). Além disso, é de cunho bibliográfico, uma vez que se fundamenta na elaboração a partir de dados já publicados, como artigos de periódicos e demais materiais (GIL, 2008).…”
Section: Rc: 41979unclassified